Variación diurna de la radiación neta de la atmósfera con las condiciones de insolación, emisividad, humedad y temperatura (ING) - Wright, Jaime (2001)
Knowledge of the energy available at the surface is of great importance in solving many scientific problems. Radiation balance provides a good estimation of this energy. Present measurements of the components of radiation balance are not always available. This work accounts for the measurements of the intensities of global, infrared and net radiation carried out for the period of three over Heredia, Costa Rica, metropolitan area. A good correlation between net and global solar radiation were obtained. The results also show a moderated correlation between net radiation and the following weather parameters: air temperature, infrared sky emittance, clearness index and water vapor pressure, and a poor correlation between net radiation and water vapor pressure and infrared sky radiation.